2022
DOI: 10.1111/imm.13550
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic inhibition of human neutrophils is exerted through D1‐like receptors and affected by bacterial infection

Abstract: Dopamine (DA) affects immune functions in healthy subjects (HS) and during disease by acting on D1-like (D1 and D5) and D2-like (D2, D3 and D4) dopaminergic receptors (DR); however, its effects on human polymorphonuclear leukocytes (PMN) are still poorly defined. We investigated DR expression in human PMN and the ability of DA to affect cell migration and reactive oxygen species (ROS) production. Experiments were performed on cells from HS and from patients (Pts) with bacterial infections as well, during the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…These data suggest that dopamine generally inhibits the production of ROS and oxidative bursts in neutrophils, particularly at higher levels. This is supported by recent data showing exposure to dopamine (10 −6 –10 −9 M) broadly inhibited neutrophil activity in a D1-dependent manner ( Marino et al, 2022 ). Further, data from hypertension studies showing that the activation of D1-like receptors, particularly D5, reduced the production of ROS in mitochondria through an autophagy-associated mechanism ( Yang et al, 2006 ; Lee et al, 2021 ).…”
Section: Dopamine and Immune Cellssupporting
confidence: 84%
“…These data suggest that dopamine generally inhibits the production of ROS and oxidative bursts in neutrophils, particularly at higher levels. This is supported by recent data showing exposure to dopamine (10 −6 –10 −9 M) broadly inhibited neutrophil activity in a D1-dependent manner ( Marino et al, 2022 ). Further, data from hypertension studies showing that the activation of D1-like receptors, particularly D5, reduced the production of ROS in mitochondria through an autophagy-associated mechanism ( Yang et al, 2006 ; Lee et al, 2021 ).…”
Section: Dopamine and Immune Cellssupporting
confidence: 84%
“…Although the present data suggest that the anti-inflammatory effects of SKF may be mainly mediated through D1-like receptors in the brain, they may also be at least partly attributed to peripheral effects because D1R is widely expressed by several types of leukocytes, 52 in which D1R activation may inhibit NLRP3 inflammasomes. 53 The expression of D1R in human and murine polymorphonuclear cells has been reported, 54 and a D1-like agonist has been shown to inhibit cell migration and ROS production. Furthermore, it is argued that DA is generated in the peripheral organs, including the lungs, affecting the immunological responses in these organs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous work addressing the effect of DRD3 stimulation in the function of NK cells provided pharmacologic evidence indicating that DRD3 signalling inhibits the cytotoxic activity of splenic NK cells in vitro [ 43 ]. Additionally, recent research has shown pharmacologic and genetic evidence indicating that signalling through the high-affinity receptor DRD5 attenuates neutrophil migration towards the infection site [ 44 ]. Therefore, the general hypothesis that low/high-affinity dopamine receptors mediate anti/pro-inflammatory mechanisms does not always work.…”
Section: Discussionmentioning
confidence: 99%